2014
DOI: 10.3389/fimmu.2014.00005
|View full text |Cite
|
Sign up to set email alerts
|

AAV Vectors Vaccines Against Infectious Diseases

Abstract: Since their discovery as a tool for gene transfer, vectors derived from the adeno-associated virus (AAV) have been used for gene therapy applications and attracted scientist to this field for their exceptional properties of efficiency of in vivo gene transfer and the level and duration of transgene expression. For many years, AAVs have been considered as low immunogenic vectors due to their ability to induce long-term expression of non-self-proteins in contrast to what has been observed with other viral vector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
116
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(119 citation statements)
references
References 76 publications
3
116
0
Order By: Relevance
“…In addition, both PEGDA and GelMA hydrogels appeared to generate pro-inflammatory response even in the absence of a polarizing stimuli, with PEGDA having a stronger effect. Although the expression and role of iNOS and Arginase-1 are better defined in mice models; recent work have also reported their expression and function in human macrophages [31, 33] .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, both PEGDA and GelMA hydrogels appeared to generate pro-inflammatory response even in the absence of a polarizing stimuli, with PEGDA having a stronger effect. Although the expression and role of iNOS and Arginase-1 are better defined in mice models; recent work have also reported their expression and function in human macrophages [31, 33] .…”
Section: Resultsmentioning
confidence: 99%
“…found that a TGF-β siRNA-loaded liposome-protamine-hyaluronic acid (LPH) nanosystem efficiently boosted the vaccine efficiency in an advanced melanoma tumor model by increasing tumor infiltrating CD8 + T cells and decreasing Tregs [120]. IDO, an enzyme that catalyzes tryptophan degradation, is also an important regulator in tumor-mediated immune tolerance [175]. T cells will undergo proliferative arrest when exposed to IDO-provoked tryptophan shortage [176].…”
Section: Application Of Nanomaterials For Tme Modulationmentioning
confidence: 99%
“…These oncogenes are constantly expressed in the HR-HPV and are responsible for the malignant transformation of cervical cancer (Azam and Shams-ul-Islam, 2010;Boccardo et al, 2010;Carter et al, 2011;Stanley, 2010;Vici et al, 2014). Therefore, the E6 and E7 genes represent the ideal targets for development of therapeutic vaccines, which potentially eliminate pre-existing lesions and malignant tumors by generating cellular immunity against HPV-infected cells (Huang et al, 2010;Kawana et al, 2012;Nieto and Salvetti, 2014).…”
Section: Introductionmentioning
confidence: 97%